"Sharing the impact of the disease": a workshop on suffering for medical students. Issue 2 (1st December 2008) - Lewis, W; Hawthorne, K
Abstract : Objectives: To investigate the attitudes of early clinical students to the concept of suffering and the work of Eric Cassell. Design: Qualitative case study using group interviews and questionnaires. Setting: A United Kingdom medical school. Participants: Two whole-year cohorts of third-year medical students (n = 557). Interventions: Group interviews involving 57 randomly selected students, with exploration of emergent themes using free text and Lickert scale questionnaires. Results: Students engaged readily with the concept of suffering and were able to identify a patient they had encountered who was suffering. Barriers to student involvement with suffering were identified. Students saw engaging with patient suffering as a clinical skill. Many students saw the ideas of Eric Cassell as plausible, although few were convinced that relief of suffering should be the central goal of medicine. Conclusions: The work of Eric Cassell formed the basis of a teaching intervention with medical students who identified engaging with suffering as a clinical skill.